Efek Peningkat Respon Imun dari Ekstrak Etanol Pegagan (Centella Asiatica Urban) pada Tikus - SRI NINGSIH; AGUNG ERU WIBOWO (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
This research had been conducted to verify the activity of ethanolic extract of Pegagan or Centella asiatica Urban (CA) from Indonesia as immune enhancing with the activity and capacity of peritoneal macrophages as parameters tested. Sprague Dawley male rats were divided into 4 groups of 5 rats each. Dose 1, dose 2 and dose 3 groups were treated with extract at the dose of 10, 20 and 40 mg/200 g b.w. p.o. for 15 consecutive days, respectively, and the control group was supplemented with carrier. One day after the last treatment, all rats were sacrificed after induced by Staphylococcus epidermidis (109 CFU per rat) i.p. and then the activity and capacity of peritoneal macrophages were examined with giemsa staining microscopically. The results showed that the immune-enhancing effect of the extract was a dose dependent manner. Based on statistical analysis (ANOVA, p < 0.05), the administration of CA extract at the dose of 40 mg/200 g bw demonstrated the highest result and differed from control group significantly (96% of macrophage activity and 61 bacteria of macrophage capacity). From these experiments could be concluded that the ethanolic extract of CA had potential to be developed as immune-enhancing agent. However, it was still needed to conduct further study for elaborating the mechanism of immune enhancer completely.